Contemporary South Asian American women's fiction: the "difference" - Assella, Shashikala Muthumal (2015)
This thesis critically explores the “difference” of contemporary South Asian American women’s fiction and their fictional narratives of women’s lives, away from the ethnic postcolonial depictions of diasporic women. The selected novels of Chitra Banerjee Divakaruni, Amulya Malladi, Bharti Kirchner, V.V. Ganeshananthan, Nayomi Munaweera, Nausheen Pasha-Zaidi and Shaila Abdullah studied here interrogate the depiction of South Asian women characters both within diasporic American locations and in South Asian settings. These writers establish individual identities that defy homogeneity assigned to regional identities and establish heterogeneous characters that are influenced through transnational travel. This dissertation’s engagement with exotic identities, foodways, ethno-social identities and diasporic and native socio-cultural pressures for women, offers a “different” reading of contemporary South Asian women’s fiction. The identities that are being reinvented by the selected Indian, Sri Lankan and Pakistani American women writers destabilise established boundaries for women’s identity in South Asian American women’s fiction by using old and new tropes such as folkloric myths, nostalgia, food and ethnic relationships. The transnational cosmopolitan locations that enable the re-negotiation of identities enable the women characters to fashion their own uniqueness. I argue that a “difference” in South Asian American women’s contemporary writing has emerged in recent times, that looks beyond ethno-social diasporic identities. These changes not only advance the already established tropes in women’s literature, but also address important issues of individuality, personal choices and societal pressure affecting self-reinvention and reception of these women within their societies. The analysis of under-researched yet powerful contemporary women writers makes this an important addition to the existing literary debates on varied women’s identities in fiction. I identify existing trends and evolving trends which help to map the emerging changes, making it a significant contribution to the understanding of the development of contemporary South Asian American women’s literature as a distinct body of work.